2015
DOI: 10.1016/j.adolescence.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and externalizing behaviors among Hispanic immigrant adolescents: Examining longitudinal effects of cultural stress

Abstract: This study examined longitudinal effects of cultural stress (a latent factor comprised of bicultural stress, ethnic discrimination, and negative context of reception) on depressive symptoms and a range of externalizing behaviors among recently (≤5 years in the U.S. at baseline) immigrated Hispanic adolescents. A sample of 302 adolescents (53% boys; mean age 14.51 years) completed baseline measures of perceived ethnic discrimination, bicultural stress, and perceived negative context of reception; and outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 73 publications
(80 reference statements)
7
120
1
Order By: Relevance
“…Overwhelmingly, the findings are based on cross-sectional data. Regression analysis was primarily used, but some employed more sophisticated methods, such as latent class analysis and latent profile analysis to create categories of various exposure variables, including discriminatory experience, cultural stressors, and coping styles [22,28,30,31,44,45]. Techniques were employed by some studies to examine potential intermediary pathways between discrimination and mental health, such as through depressive symptoms or anxiety [19,24,43,46], avoidant coping strategies [33,47], trans diagnostic factors [48], general stress [40], stronger belief in an unjust world [49], acculturation-related and social support variables [13,50,51], anger [46], prosocial behavior [33], and perfectionism [52].…”
Section: Resultsmentioning
confidence: 99%
“…Overwhelmingly, the findings are based on cross-sectional data. Regression analysis was primarily used, but some employed more sophisticated methods, such as latent class analysis and latent profile analysis to create categories of various exposure variables, including discriminatory experience, cultural stressors, and coping styles [22,28,30,31,44,45]. Techniques were employed by some studies to examine potential intermediary pathways between discrimination and mental health, such as through depressive symptoms or anxiety [19,24,43,46], avoidant coping strategies [33,47], trans diagnostic factors [48], general stress [40], stronger belief in an unjust world [49], acculturation-related and social support variables [13,50,51], anger [46], prosocial behavior [33], and perfectionism [52].…”
Section: Resultsmentioning
confidence: 99%
“…Although cultural transactions can be positive (Cano, Vaughan, de Dios, Castro, Roncancio, & Ojeda, in press) or negative (Cano et al, 2015), we focused on negative cultural transactions. This follows from Acculturation Strain Theory , which proposes that enthnocultural orientation, operationalized as a unidimensional continuum of acculturation, is associated with increased experience of cultural stressors that in turn contribute to substance use and poor mental health outcomes (Vega, Zimmerman, Gil, Warheit, & Apospori, 1997).…”
Section: Cultural Transactionsmentioning
confidence: 99%
“…Unidimensional cultural constructs and broad measures of acculturation have been examined in relation to substance use initiation (Grigsby, Forster, Soto, & Unger, ) and continued use (Prado, Szapocznik, Maldonado‐Molina, Schwartz, & Pantin, ) among Hispanics; however, the influence of specific cultural factors on AOD attitudes among immigrant Hispanic samples remains scant. Recent research has demonstrated that cultural influences work in concert rather than in isolation (Cano et al., ; Flay, Snyder, & Petraitis, ), but empirical evidence is limited and further replication among immigrant samples.…”
Section: Introductionmentioning
confidence: 99%